Master's student of the "World History" department of Samarkand State University - Aslamkulova Parvina Jamshidovna (Western European Studies, 2023)
The Wars of Religion (French Guerres de Religion) or Huguenot Wars were a series of 32-year-old civil wars between Catholics and Protestants (Huguenots) that tore apart the French state during the last kings of the Valois dynasty, the Huguenots being led by Henry of Navarre (Prince of Condé) of the Bourbon dynasty and Admiral de Colig led by The Catholics were led by Catherine de' Medici, the mother of the French queen, and the powerful Guises. His neighbors tried to influence the course of events in France – Queen Elizabeth Tudor of England supported the Huguenots, and King Philip of Habsburg of Spain supported the Catholics. The wars ended with the accession of the Catholic Henry of Navarre to the French throne and the publication of the Edict of Nantes (1598). This article describes the history of the religious war in France and the social and political relations that followed
Keywords: Reformation; France; Catholics; Huguenots